2017
DOI: 10.1247/csf.17003
|View full text |Cite
|
Sign up to set email alerts
|

PI5P and PI(3,5)P<sub>2</sub>: Minor, but Essential Phosphoinositides

Abstract: In most eukaryotes, phosphoinositides (PIs) have crucial roles in multiple cellular functions. Although the cellular levels of phosphatidylinositol 5-phosphate (PI5P) and phosphatidylinositol 3,5-bisphosphate (PI(3,5)P2) are extremely low relative to some other PIs, emerging evidence demonstrates that both lipids are crucial for the endocytic pathway, intracellular signaling, and adaptation to stress. Mutations that causes defects in the biosynthesis of PI5P and PI(3,5)P2 are linked to human diseases including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
126
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 131 publications
(227 reference statements)
4
126
1
1
Order By: Relevance
“…While the majority of PI-4,5-P2 is generated by phosphorylation of phosphatidylinositol 4phosphate (PI-4-P) on the 5-position by the Type I PI4P5K kinases, a PI5P4K-driven alternate route was discovered in 1997, hence the designation Type II (Rameh et al, 1997). The PI5P4Ks were traditionally thought to mainly be crucial direct regulators of PI-5-P levels Stijf-Bultsma & Sommer et al, 2015;Hasegawa, Strunk, & Weisman, 2017) however, PI5P4Kα was found to synthesize a pool of PI-4,5-P2 that is specifically important in mTORC2 regulation (Bulley et al, 2016) and to play a critical role in intracellular cholesterol transport by modulating PI-4,5-P2 homeostasis on peroxisome membranes (Hu et al, 2018). The low-activity isoform PI5P4Kγ was demonstrated to positively regulate Notch1 signaling by facilitating receptor recycling, suggesting that endosome-localized production of PI(4,5)P2 is involved Notch transport (Zheng & Conner, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of PI-4,5-P2 is generated by phosphorylation of phosphatidylinositol 4phosphate (PI-4-P) on the 5-position by the Type I PI4P5K kinases, a PI5P4K-driven alternate route was discovered in 1997, hence the designation Type II (Rameh et al, 1997). The PI5P4Ks were traditionally thought to mainly be crucial direct regulators of PI-5-P levels Stijf-Bultsma & Sommer et al, 2015;Hasegawa, Strunk, & Weisman, 2017) however, PI5P4Kα was found to synthesize a pool of PI-4,5-P2 that is specifically important in mTORC2 regulation (Bulley et al, 2016) and to play a critical role in intracellular cholesterol transport by modulating PI-4,5-P2 homeostasis on peroxisome membranes (Hu et al, 2018). The low-activity isoform PI5P4Kγ was demonstrated to positively regulate Notch1 signaling by facilitating receptor recycling, suggesting that endosome-localized production of PI(4,5)P2 is involved Notch transport (Zheng & Conner, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Each cDNA in the final plasmid was sequencevalidated in its entirety, and expression of the full-length fusion protein in HEK293 cells was mol % of one of six PIPs: PI(3)P, PI(4)P, PI(5)P, PI(3,4)P2, PI(4,5)P2, and PI (3,4,5)P3. The only PIP omitted in our assays was PI(3,5)P2 due to scarce evidence in the literature for its specific recognition by proteins (17) and the lack of a reliable positive control. Vesicles containing 5% phosphatidic acid (PA), a different type of signaling lipid than PIPs, were also included in our assays.…”
Section: Lipid-simpull Assay For Human Ph Domain Proteinsmentioning
confidence: 99%
“…The noncanonical PI(5)P-dependent pathway can compensate the absence of PI(3)P, e.g. due to defective Vps34, or overrule PI(3)P in particular circumstances, such as glucose starvation [82,83]. It also been reported that PI(3,5)P 2 is required for completion of basal autophagy, particularly in mouse models of neurodegeneration.…”
Section: Autophagic Cell Deathmentioning
confidence: 99%